ANALYSIS OF THE INFORMATION AND TELECOMMUNICATION COMPONENT OF SUPPORT AND DECISION-MAKING SYSTEM - Юдін, О.; Луцький, М.; Рогоза, І. (Science-based technologies, 2012)
As a result of scientific research the ways of further qualitative modernization of the control  system are set,  the priority tasks that are connected with providing terms of efficiency and reliability of the use of the control systemare defined. The necessity of establishing the system of acceptance and support solutions on which rely the functions of collection, processing, storage, transmission  and analysis of information from different  sources  of messages is justified.